2011
DOI: 10.1111/j.1365-2621.2010.02518.x
|View full text |Cite
|
Sign up to set email alerts
|

Proximate, mineral, amino acid, fatty acid, vitamin E, phytate phosphate and fibre composition of Mimusops zeyheri (Red Milkwood) seed

Abstract: Mimusops zeyheri, an indigenous tree widely distributed in sub-Saharan Africa, provides edible fruit. Research on the tree has focused on fruit pulp composition and uses. This study evaluated the nutritional potential of M. zeyheri seed by determining the proximate, fibre and phytate-phosphate content, the amino acid and fatty acid profiles and vitamin E content of the seed. Dry matter, organic matter, crude protein, ether extract and ash constituted 91.1%, 88.3%, 9.3%, 25.6% and 2.8% of the seed mass respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…It is rich source of vitamin c. (Chivandi, Davidson, Pretorius, & Erlwanger, 2011) It is a large, evergreen plant that may reach 15 m in height. (Department of Agriculture Forestry and Fisheries (DAFF), 2012; Mabhaudhi, Chimonyo, Chibarabada, et al, 2017) Ripe fruits are often edible.…”
Section: General Uses Morphological Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is rich source of vitamin c. (Chivandi, Davidson, Pretorius, & Erlwanger, 2011) It is a large, evergreen plant that may reach 15 m in height. (Department of Agriculture Forestry and Fisheries (DAFF), 2012; Mabhaudhi, Chimonyo, Chibarabada, et al, 2017) Ripe fruits are often edible.…”
Section: General Uses Morphological Descriptionmentioning
confidence: 99%
“…Fatty acids: Palmitic acid, myristic acid, stearic acid, oleic acid, linoleic acid, palmitoleic acid, arachidic acid, heptadecanoic acid, and behenic acid (Joseph et al, ) Antinutrient: Tannin, oxalate, phytate, and trypsin inhibitor (Adesuyi, Elumm, Adaramola, & Nwokocha, 2012) Phytochemicals: Phenol, saponin, alkaloids, flavonoids, and glycosides (Adesuyi et al, 2012) Mimusops zeyheri Sond Fatty acid: Palmitic acid, oleic acid, and linoleic acid (Chivandi et al, 2011) Amino Acids: Arginine, serine, aspartic acid, glutamic acid, glycine, threonine, alanine, tyrosine, proline, hydroproline, methionine, valine, phenylalanine, isoleucine, leucine, histidine, and lysine (Chivandi et al, 2011) Parinari curatellifolia Planch.ex Benth.…”
Section: Garcinia Livingstonei T Andersonmentioning
confidence: 99%
“…While the CP content of full fat M. caffra seed (10.02 ± 0.16%) was within the CP ranges reported by Li et al (2014) and Bhuiyan et al (2012) for maize grain, the DM, EE and ash content of the M. caffra seed were higher compared to those of maize grain. The full fat Mimusops zeyheri seed, an upland cousin of M. caffra, had a reported CP content of 9.3% (Chivandi et al, 2011a) which is comparable to that of the CP content of full fat M. caffra seed. However, when compared to the CP content of full fat seeds from other indigenous fruit bearing trees found in SSA, for example, Kigelia africana at 37.5% (Chivandi et al, 2011b), Ximenia caffra at 18.3% (Chivandi et al, 2012) and Terminalia sericea at 46.2% (Chivandi et al, 2013), M. caffra seed has lower CP content.…”
Section: Potential As Food/feed Ingredientmentioning
confidence: 83%
“…Although lower than the oil yield from sunflower and cotton seed, oil yield from M. caffra seed (26%) is comparable to soybean. When compared to M. zeyheri, its upland cousin, whose seed has a reported seed oil yield of 21.3% (Chivandi et al, 2011a(Chivandi et al, , 2011b, M. caffra seed has a higher seed oil yield. Due to its interesting fatty acid profile, the potential of M. caffra seed oil as a novelty raw material for community-based cottage industries needs to be explored.…”
Section: Potential As a Non-conventional Plant Oil Sourcementioning
confidence: 89%
“…Sub-Saharan Africa is richly endowed with indigenous fruit bearing trees (IFBTs) whose seeds are potential sources of nutrients (Chivandi et al., 2010). The Red milkwood ( Mimusops zeyheri), an IFBT, is widely distributed in SSA ( Janick & Paull, 2008 ) and its fruit pulp is consumed by animals, birds and humans ( Chivandi, Davidson, Pretorius & Erlwanger, 2011 ). Findings from our laboratory have shown that the seed meal from dehulled M. zeyheri seed has a protein content (9.3%) similar to that of maize but a higher energy (24.34±0.56 MJ/kg DM vs 17 MJ/kg DM) and calcium content ( Chivandi, Davidson & Erlwanger, 2011 ).…”
Section: Introductionmentioning
confidence: 99%